BUDAYA HUKUM TERHADAP PENEGAKAN HUKUM DALAM PENERAPAN UU ITE DI INDONESIA - Silalahi, Andreas Parasian; Maulana, Ifan; Sari, Elsi Kartika (Ensiklopedia Education Review, 2024)
Abstract: This research discusses the influence of Indonesian legal culture on the enforcement of the Information and Electronic Transactions Law (UU ITE). The background explains the shift in societal interactions due to developments in information technology followed by new challenges, such as the spread of false information and hate speech. The ITE Law, which was designed to create a safe digital space, has received criticism for potentially limiting freedom of expression. The creation of legal cases involving the public in the implementation of the ITE Law shows that there is a dilemma related to the existing legal culture, where if the public respects the regulations, law enforcement can be effective, but if there is skepticism, the implementation can be counterproductive. This research also covers aspects of public understanding and awareness, reactive legal culture, as well as challenges for law enforcement in understanding technological developments. In conclusion, the form of interaction between legal culture and the implementation of the ITE Law in Indonesia shows the complexity that influences public trust in the law and its enforcement process, thus creating the phenomenon of self-surveillance in the digital realm.Keywords: Legal culture, Law Enforcement, Implementation of the ITE Law